2020
DOI: 10.18267/j.pep.731
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Trade as a Tool to Strengthen the EU's Competitiveness Against China (A Case of the Service Sector)

Abstract: The paper analyses some aspects of EU-China trade relations. Correlation analysis was applied to quantify the extent of the influence of the foreign trade with China on the overall foreign trade of the five members of the EU that have the largest foreign trade with China. Given the ongoing trade deficits of the EU with China, we decided to apply the Trade Complementarity Index (TCI) to determine the extent of their trade complementarity. Our initial hypothesis that the economies are highly complementary was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Research on the topic undertaken by Tang et al (2014) found that China's comparative advantage in services lies in tasks requiring relatively low levels of skill, knowledge, and productivity. Similar results were obtained by Baláž et al (2020), who also observed that China's competitiveness of selected sectors derives from a lower level of sophistication. On the other hand, Kung et al (2016) analysed China's comparative advantage in trade in services taking into consideration twelve main types of services and found that China is considerably less competitive in trade in services than other countries in the study.…”
Section: Literature Reviewsupporting
confidence: 84%
See 2 more Smart Citations
“…Research on the topic undertaken by Tang et al (2014) found that China's comparative advantage in services lies in tasks requiring relatively low levels of skill, knowledge, and productivity. Similar results were obtained by Baláž et al (2020), who also observed that China's competitiveness of selected sectors derives from a lower level of sophistication. On the other hand, Kung et al (2016) analysed China's comparative advantage in trade in services taking into consideration twelve main types of services and found that China is considerably less competitive in trade in services than other countries in the study.…”
Section: Literature Reviewsupporting
confidence: 84%
“…As China's trade in services has developed, trade relations between China and the European Union have become more extensive over the years. This growth creates some concerns, however, Baláž, et al (2020) argue that the intensity of trade in services with China remains at a relatively low level. As Holslag (2017) noted, China's share in trade in services markets is growing spectacularly in countries situated along the New Silk Road and is becoming a major challenge and threat to European countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…V. Ružeková, Z. Kittová and D. Steinhauser [2020] used this model to quantify and qualify the impact of the institutional environment on the export performance of a country. On the basis of this model, P. Baláž, M. Královičová and D. Steinhauser [2020] assessed the growth potential of trade in services between the EU and China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But De Jonquières (2016) warns that the EU should see the BRI not as some giant leap forward -as the Chinese side often portrays -but as a series of small steps aimed at fostering steadily closer engagement with China. Baláž, Královičová, and Steinhauser (2020) claimed that it will be crucial for the future of the EU to find a way to cooperate effectively with China so that it is a mutually beneficial cooperation, which will bring prosperity to both trade partners. On the other hand, Casarini (2016) talks about major political challenge for the EU.…”
Section: Literature Reviewmentioning
confidence: 99%